Is informal charcoal production necessarily unsustainable? A comparison of three oak management systems in the central Mexican Sierras. - Guzmán-Sánchez, Javier; Mwampamba, Tuyeni Heita (Renewable Energy, Biomass & Sustainability, 2020)
A steady increase in charcoal production as an energy source is expected (FAO, 2017). Its negative effects due to above-ground biomass removal (BSS) suggest favoring conservation (Lee and Lautenbach, 2016; Monárrez- González, et.al., 2018). However, sustainable forest management [SFM] allows considering charcoal as a renewable source of energy (Antinori and Rausser, 2010; Camou-Guerrero, et.al., 2014; Sist, et.al., 2014; Aguirre-Calderón, 2015; FAO, 2017; Ramírez, 2017). Mexican regulations focus SFM on functionality, industrialization and large scale (Antinori and Rausser, 2010; Deschamps and Madrid, 2018; Cravioto, 2019); informality is considered unsustainable due to irregular and poor management practices (Sist, et.al., 2014; Monárrez- González, et.al., 2018). We analyzed impacts of three oak management systems on tons of BSS: [1] conservation, [2] formal production, and [3] informal production; influenced by [1] advantageous (nursery), and [2] disadvantageous (drying shed) biophysical conditions. We focused on verifying the existence of differences in BSS and structure between systems and conditions. With such analysis, we reconsider the bias towards conserving and the dismissal of informality as unsustainable.